Book Review of The Bluest Eye written by Toni Morrison - Paramita, Dana (LANTERN (Journal on English Language, Culture and Literature), 2015)
The writer chooses The Bluest Eye because this novel is challenging to be reviewed. The controversial nature of the book, which deals with racism, incest, and child molestation, makes it being one of the most challenged books in America’s libraries – the ones people complain about or ask to be removed, according to The American Library Association (http://www.ew.com/article/2015/04/14/here-are-american-library-associations-10-most-complained-about-books-2014). On the other hand, the story of The Bluest Eye is interesting because the story tells about an eleven year old African American girl who hates her own self due to her black skin. She prays for white skin and blue eyes because they will make her beautiful and allow her to see the world differently, the community will treat her better as well. The story is set in Lorain, Ohio, against the backdrop of America's Midwest during the years following the Great Depression.The Bluest Eye is Toni Morrison's first novel published in 1970.